Supersólidos dipolares com polarização arbitrária - Oliveira Neto, José Fernandes de (2021)
Supersolids represent a new state of matter in which quantum effects play a crucial role, leading to the simultaneous exhibition of both superfluidity and crystalline order, associated with the spontaneous breaking of gauge and translation symmetries, respectively. Although thought to exist in He-4 since the 50s, its experimental realization has only been confirmed in 2019, in atomic systems of dipolar quantum droplet made out of Dy-164 and Er-166. This motivated several theoretical and experimental investigations. In this dissertation, we present a theoretical contribution for the ground state of these supersolids, considering an arbitrarily oriented external field. In this context, by choosing an appropriate wavefunction that takes into account the phase coherence needed in the definition of a supersolid, we investigate the influence of this orientation on the transition from a Bose-Einstein condensate to a one-, two-, and multi-system droplets. Thus, we seek to characterize the phase diagram containing supersolid and non-supersolid states of these systems. Specifically for the configuration with several droplets, using the point dipole approximation, we also investigate the possibility of new lattice geometries, other than the traditional triangular lattice observed experimentally. In the first case, through the construction of the phase diagram, we obtained that the field orientation actually induces the indicated transitions, leading also to a new class of condensates with spatial modulation, not yet reported in the literature. In the second, on the other hand, our data are still inconclusive to predict new lattice geometries, but a qualitatively new behavior has already been identified.